The role of cGAS-STING signaling in HPV infection and HPV-related cancers - Zhu, Qiugang; Yu, Shiyi (Frontiers in Immunology, 2025)
Human papillomavirus (HPV) is a highly prevalent virus that primarily infects human epithelial cells, resulting in a significant health burden by causing conditions such as anogenital warts, cervical cancers, and head and neck squamous cell carcinoma. Although vaccination has been implemented for cancer prevention, a thorough understanding of anti-HPV immunity remains of critical importance for HPV-related disease management. The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway forms a key signaling cascade within the innate immune system, which is activated by cytosolic DNA and functions through the production of type I interferon (IFN-I). Accumulating evidence indicates a correlation between the cGAS-STING pathway and HPV infection, as well as HPV-related malignancies, suggesting its potential as a promising therapeutic target. This review discusses the role of the cGAS-STING signaling pathway in HPV infection and HPV-related cancers, as well as potential therapeutic strategies that target this pathway.